Twist and Degrade—Impact of Molecular Structure on the Photostability of Nonfullerene Acceptors and Their Photovoltaic Blends. Issue 15 (21st February 2019) - Luke, Joel; Speller, Emily M.; Wadsworth, Andrew; Wyatt, Mark F.; Dimitrov, Stoichko; Lee, Harrison K. H.; Li, Zhe; Tsoi, Wing C.; McCulloch, Iain; Bagnis, Diego; Durrant, James R.; Kim, Ji‐Seon
Abstract: Nonfullerene acceptors (NFAs) dominate organic photovoltaic (OPV) research due to their promising efficiencies and stabilities. However, there is very little investigation into the molecular processes of degradation, which is critical to guiding design of novel NFAs for long‐lived, commercially viable OPVs. Here, the important role of molecular structure and conformation in NFA photostability in air is investigated by comparing structurally similar but conformationally different promising NFAs: planar O‐IDTBR and nonplanar O‐IDFBR. A three‐phase degradation process is identified: i) initial photoinduced conformational change (i.e., torsion about the core–benzothiadiazole dihedral), induced by noncovalent interactions with environmental molecules, ii) followed by photo‐oxidation and fragmentation, leading to chromophore bleaching and degradation product formation, and iii) finally complete chromophore bleaching. Initial conformational change is a critical prerequisite for further degradation, providing fundamental understanding of the relative stability of IDTBR and IDFBR, where the already twisted IDFBR is more prone to degradation. When blended with the donor polymer poly(3‐hexylthiophene), both NFAs exhibit improved photostability while the photostability of the polymer itself is significantly reduced by the more miscible twisted NFA. The findings elucidate the important role of NFA molecular structure in photostability of OPV systems, and provide vital insights into molecular design rules for intrinsically photostable NFAs. Abstract : Nonfullerene acceptors (NFAs) provide an exciting prospect for organic solar cells; however, their stability still lacks fundamental understanding. The promising high‐efficiency NFAs, IDTBR and IDFBR, show a three‐phase degradation mechanism, which involves a strong initial molecular conformational change prior to photodegradation under light and oxygen stress, indicating the important role of NFA molecular structure in solar cell stability.